Experiences of Spouses of Women with Mastectomy Resulting From Breast Cancer in the Accra Metropolis - Kotei, B. A. (University of Ghana, 2015)
Breast Cancer is the leading cause of death and most commonly diagnosed cancer in women. The most common treatment is surgery in the form of mastectomy. Breast Cancer (BC) and mastectomy does not affect the well-being of only the woman but also that of the husband or partner. Breast cancer is therefore referred to as a couple‟s disease. The purpose of this study was to explore the experiences of spouses of women with mastectomy as a result of their wives‟ BC in the Accra Metropolis. The Quality of Life Model Applied to Family Caregivers by Betty Ferrell was the organizing framework for this study. A qualitative exploratory descriptive design was employed. A purposive sampling technique was used and data were saturated with the twelfth participant. Data were collected with a semi-structured interview guide. All interviews were audio taped and transcribed verbatim. Data were analyzed using thematic content analysis. During the study, anonymity and confidentiality were ensured. The four themes stipulated by the model; physical, social, psychological and spiritual well-being of spouses was identified. Emerging themes were support and spousal involvement in diagnosis and treatment. Few of the men experienced sleep disruption and fatigue. The relationship of most of the spouses with their wives became better after the surgery. Spouses feared their wives could die during surgery. Spiritually, spouses derived meaning and hope from God. The spouses gave their wives domestic and emotional support. Most of the spouses were actively involved in the treatment and diagnosis of their wives. It was recommended that spouses be included in the provision of care for women with BC and educational material should be prepared and given to the spouses.
Thesis (MPhil.) - University of Ghana, 2015
xiii, 114p. : ill.